Reducing Elective Surgery Backlogs Through Centralized Waiting List Management: A Quality Improvement Study. - Daoud, Rabbani Mahmoud; Alhoda, Moosa; Jasim, Zainab; Fredericks, Salim; Kause, Juliane (Inquiry (00469580), 2026)
Introduction: Growing elective surgical waiting lists remain a persistent global challenge, exacerbated by the COVID-19 pandemic, which led to the widespread suspension of non-urgent procedures. In the Gulf region, elective surgery cancellation rates reached up to 72% by 2020, compounding surgical backlogs. At Salmaniya Medical Complex, Bahrain's largest public tertiary hospital, the resulting backlog overwhelmed existing systems that relied on fragmented spreadsheets and manual logs. This Quality Improvement Project (QIP) aimed to improve surgical waiting list management using a centralized, data-driven approach to reduce backlog, improve scheduling, and enhance theatre utilization. Methods: This retrospective pre-post QIP included all adult patients (≥18 years) listed for elective, non-cancer surgery across secondary and tertiary surgical specialties between January 2019 and December 2023. Interventions, implemented from January to August 2024, included: (1) consolidating all waiting list data into a single computerized system; (2) validating and updating entries through direct patient contact; and (3) integrating a centralized repository within the Electronic Patient Record (EPR) system. This enabled real-time tracking, automated prioritization, and flexible scheduling. The primary outcome was waiting list volume. Secondary outcomes were mean waiting time to surgery and theatre utilization. Descriptive statistics and paired t-tests were applied to assess the significance of any differences observed with a significance of p<0.05. Results: From January to August 2024, the surgical waiting list decreased by 51.74%, from 9,597 to 4,627 patients. Major reductions (relative to the baseline waiting list) were observed in Ophthalmology (69.40%), Urology (59.23%), and Orthopedics (58.59%). Mean waiting times (SD) decreased from 12.7 (7.72) to 7.2 (4.75) months (p = 0.014), corresponding to a 158-day reduction. Mean monthly caseload in the main operating theatres (MOT) increased from 1,469 (139.3) cases in 2023 to 1,608 (94.4) in 2024 (p < 0.001). Conclusion: A centralized, EPR-integrated surgical waiting list system significantly reduced surgical backlogs and delays, while improving coordination, prioritization, and theatre utilization. Differences in outcomes across departments reflect varying case complexities and highlight the need for tailored strategies. This scalable model supports more efficient post-pandemic recovery and long-term service resilience.